Serbia in Yugoslavia in 1986/1987 – Content Analysis of Texts Published in Periodicals - Baščarević, Ivan M. (Sociološki pregled, 2019)
This research paper is the result of the research of the print media Književne novine, Književna reč, Pravoslavlje, NIN and Duga in the course of 1986/1987 by using the method of content analysis. The research was conducted on the complete available material for the years 1986 and 1987. In some parts of the text and in the context of events, the analysis included printed media that are outside of the timeline of this research. By analysing the content of the abovementioned periodicals, the author concluded that the Serbian intelligentsia was homogenous in protecting Serbian national interests in Kosovo and Metohija. This can largely be attributed to complex social and political circumstances in which the population of Serbs, clergy and monks, as well as the sacral property of the Serbian Orthodox Church in Kosovo and Metohija, were exposed to constant violence by the Albanian majority. Under such conditions, the Kosovo myth served to the Serbian intelligentsia as the cultural foundation for the homogenization of national consciousness. In addition, according to the legal restrictions imposed by the 1974 Constitution, the Socialist Republic of Serbia was politically powerless to resolve the evident issues arising in Kosovo and Metohija. The Serbian intelligentsia, namely journalists, writers, artists, scientists, academicians and clergy of the Serbian Orthodox Church, tried to make up for such political vacuum. By highlighting the Kosovo myth and raising the Serbian national question, the public opinion in Serbia was created that it was necessary to redefne the national position of Serbs in the SFRY.Keywords: Kosovo and Metohija, Serbia, Yugoslavia, the Serbian intelligentsia, the Kosovo myth, patriotism.